Monitoring Concept of the Information Support System Organization of the Anti-Crisis Management of the Regional Agro-Industrial Complex - Kitovich Tkhakushinov, Edward; Aslanovna Khachemizova, Emma (International Journal of Engineering and Technology, 2018)
The article is devoted to the problems of ensuring efficient management of the agro-industrial complex (AIC) in the region and a systematic analysis of economic processes in crisis situations. The authors discuss the anti-crisis management system involving the formulation of necessary solutions aimed at supporting the subjects of the AIC in economic equilibrium, based on having an effective monitoring mechanism. This management system ensures a rapid response to sudden changes in economic factors and offers a set of alternative solutions to determine the strategy and tactics of the AIC development.The monitoring concept of anti-crisis management is justified, based on the organization of a powerful monitoring mechanism, enabling timely, necessary and sufficient analysis of the processes and patterns of managing socio-economic processes. At the same time, a special role is given to interaction between design and expert assessments of the factors of crisis situations, making it possible to characterize the degree of influence of a crisis change in the conditions of the external environment on the economy of the subjects and the whole AIC in general.Â Â